Religiosity and Psychological Well-Being of School Counselors - Syahril Syahril; Sitti Riadil Janna (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the effect of religiosity on the psychological well-being of school counselors. The majority of counsellors report experiencing mental health issues such work-related stress, exhaustion, anxiety, and emotional disturbances like impatience and irritation while doing their jobs. The counselor's mental condition is an indication of their poor mental health. Methodologically, this investigation was a quantitative study employing a correlational approach. Statistical regression analysis was used to examine the collected data. The research sample was school counsellors in South Sulawesi, totalling 103 counsellors for SMP/MTs, and SMA/SMK/MA. The research instrument used the Centrality of Religiosity Scale (CRS) and the Psychological Well-being Scale. The results showed that there was an influence of religiosity on the psychological well-being of school counsellors. The limitation of this study is that the respondents are public school counsellors and not private school counsellors. Therefore, further research can use a sample of private school counsellors and examine other variables in improving the psychological well-being of counsellors.